Providing Skills for the Knowledge Economy : The World Bank in Tertiary Education in Latin America and the Caribbean - Holm-Nielsen, Lauritz B.; Blom, Andreas; Garcia, Patricia (World Bank, Washington, DC, 2012)
Knowledge based economies have an advantage in today's liberalized global market. OECD countries with extensive knowledge assets are able to drive rapid technological progress and reap the benefits in economic growth and rising living standards. Yet, Latin American and Caribbean (LAC) countries struggle to provide their citizens with the educational levels and advanced skills needed to create and apply new knowledge. Recent empirical work by Sanchez-Paramo and Schady (2002) documents a remarkable shift in labor demand towards advanced skills in LAC countries. Producing skilled and knowledgeable people requires a strong education system, including access to good secondary and tertiary education. This note provides information about World Bank assistance to LAC countries to increase access to quality tertiary education.